HIEROTOPY AS A SUBJECT OF CULTUROLOGICAL ANALYSIS - Катерина Шевчук (Докса, 2017)
The attempt of analysis of hierotopy in the context of cultural studies has been made in the article. It is stated that hierotopy is a creation of specific sacred spaces and regarded as a special kind of creative activity, as well as a special area of historical and cultural researches, in which the examples of this creativity are identified and analyzed. It is shown that there are several reasons for the sanctity of the place. Among them there should be distinguished the Commission of the ritual in the place, the consecration of the site directly by God through indication, the promise to God, the appearance of theophany, or sanctification by it after construction of the topos. The reason may be the special natural conditions, reminding people about the greatness of God, or legends associated with a single object on the ground; the practical need to build in a particular location due to the convenience or availability of earlier religious buildings of other faiths. After identification of the location as the sacred its transformation begins in accordance with the rules or norms of culture and religion. It is shown that such transformations are sound and light effects, shape, space, smell, symbols, priests’ clothing, religious ceremony and festivals, folk traditions.